Can Waist Circumference Be a Reliable Anthropometric Parameter in Healthy Normal Weight and Overweight Adolescents? - Nebojsa KAVARIC; Aleksandra KLISIC; Ivan SOLDATOVIC; Bojko BJELAKOVIC (Tehran University of Medical Sciences, 2015)
Letter to the Editor